2009
DOI: 10.3389/neuro.08.024.2009
|View full text |Cite
|
Sign up to set email alerts
|

Early life stress as an influence on limbic epilepsy: a hypothesis whose time has come?

Abstract: The pathogenesis of mesial temporal lobe epilepsy (MTLE), the most prevalent form of refractory focal epilepsy in adults, is thought to begin in early life, even though seizures may not commence until adolescence or adulthood. Amongst the range of early life factors implicated in MTLE causation (febrile seizures, traumatic brain injury, etc.), stress may be one important contributor. Early life stress is an a priori agent deserving study because of the large amount of neuroscientific data showing enduring effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 216 publications
2
54
0
Order By: Relevance
“…Indeed, the results obtained when brain morphological changes were prevented suggest that all treatments, even nonpharmacological treatments, suppressing residual traces in the hippocampus and the amygdala should also suppress vulnerability to the development of depressive disorders. Such changes may be extended to other diseases in which life stressor events predispose individuals to develop, for instance, epilepsy (Koe et al, 2009) or schizophrenia (Cannon et al, 2003). Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the results obtained when brain morphological changes were prevented suggest that all treatments, even nonpharmacological treatments, suppressing residual traces in the hippocampus and the amygdala should also suppress vulnerability to the development of depressive disorders. Such changes may be extended to other diseases in which life stressor events predispose individuals to develop, for instance, epilepsy (Koe et al, 2009) or schizophrenia (Cannon et al, 2003). Figure 8.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review (Koe et al 2009) found seven rodent studies reporting long-term effects of early life stress on epilepsy-relevant outcomes (e.g., seizure threshold, kindling rate). Of these, two studies employed prenatal stressors (e.g., restraint), four employed postnatal stressors (maternal separation, neonatal isolation (from both mother and siblings), cross-fostering), and one study used both.…”
Section: Focal Limbic Epilepsymentioning
confidence: 99%
“…This in turn has motivated an immense body of experimental work in animal models, mainly rodent and primate studies, showing fairly consistent, often large effects of stressors and stress mediators on brain, often enduring well into later adult life. We and others have shown that early life stress increases vulnerability to limbic epilepsy in adult life (Koe et al 2009). In early life stress research, a variety of experimental models are employed, such as prenatal glucocorticoid administration, postnatal separation of pups from dams (or from both dams and siblings), or restriction of the dam's access to nesting material (Sanchez et al 2001;Weinstock 2008), and much is known about intervening mechanisms, although vastly more remains to be understood McEwen 2008;Oitzl et al 2010).…”
Section: Introductionmentioning
confidence: 96%
“…The vulnerable population was identified to have low serum levels of brain-derived neurotrophic factor (BDNF) and increased circulating levels of corticosterone. Treating animals with the BDNF analog, 7-8-dihydroxyflavone (7, or the antidepressant imipramine during the "second hit" prevented the elevations in corticosterone and the adverse behavioral consequences, including depression-like behavior and anhedonia. These data suggest that low levels of BDNF play a critical role in allostatic load in adult animals and vulnerability to depression.…”
Section: Primed For Problems: Stress Confers Vulnerability To Epilepsmentioning
confidence: 99%
“…For example, maternal separation induces long-lasting effects on seizure susceptibility and increased propensity for epileptogenesis (for a review, see [7]). A recent study demonstrated that early life stress due to maternal separation exacerbated the seizure-induced elevations in corticosterone levels, reduced seizure threshold, and increased seizure severity (4).…”
mentioning
confidence: 99%